Best practices in infection prevention and control an international perspective - Soule, Barbara M.; Memish, Ziad A.; Malani, Preeti N. (IG library, 2012)
An infection prevention and control (IPC) resource for health care organizations. It provides thorough analysis of Joint Commission International (JCI) infection prevention and control requirements, as well as case studies, tips, and tools for increasing IPC compliance and patient safety.